From Better Access to Better Outcomes: Integrating Logotherapy With Focused Psychological Strategies - Kyra J. Dawbarn; Paul McQuillan (Psychotherapy and Counselling Journal of Australia)
The Better Access to Psychiatrists, Psychologists and General Practitioners through the Medicare Benefits Schedule (Better Access) initiative was introduced by the Australian Government to improve outcomes for people with a clinically diagnosed mental health condition through evidence-based treatment. Under this initiative, Government Medicare rebates are available to patients for services provided by approved practitioners using the Focused Psychological Strategies, which are specific mental health treatment strategies derived from evidence-based psychological therapies: psycho-education (including motivational interviewing), cognitive-behavioural therapy, relaxation strategies, skills training, interpersonal therapy, and narrative therapy (for clients of Aboriginal and Torres Strait Islander descent). This paper outlines how logotherapy, as an adjunct therapy to other approaches, can help ensure that Better Access leads to better outcomes for clients.